Piloting moringa agribusiness to improve villagers’ economic community - Wijaya, Oki; Rahayu, Lestari; Rokhim, Nur; Yusmiastuti, Tsaniya; Utama, Surya Aditya (Journal of Community Service and Empowerment, 2021)
This activity was motivated by the low economic status of the village community, which is located far from the center of the district capital. On the other hand, there is potential for the development of kelor (Moringa) in the village. This community service was carried out with the aim of improving the community's economy through Moringa agribusiness in Pilangrejo Village, Nglipar District, Gunung Kidul Regency. This activity was carried out in January-June 2020, in Danyangan Hamlet, Pilangrejo Village, Nglipar District, Gunungkidul Regency. This activity was attended by the people of Danyangan Hamlet, both men and women. The male participants were those who make a living as farmers. While the female participants were housewives who do not have any permanent livelihood. The number of primary participants were 10 people who were community leaders in Pilangrejo Village. The implementation stages of activities include kelor planting and seedling, training on post-harvest processing, and providing production tool. The implementation of this activity is based on subsystems in agribusiness, namely the upstream (input) subsystem, on-farm subsystem and downstream subsystem. The results of this activity can be said that the piloting of Moringa agribusiness can be one solution that can be done in an effort to improve the economy of the community in Danyangan Hamlet, Pilangrejo Village, Gunung Kidul Regency. The benefits that can be obtained in this activity include the sale of Moringa powder and the use of Moringa as the main menu in the community's food pattern.